Optimizing Hospital Bed Capacity and Resource Allocation Using Inflow and Outflow Indices for Effective Healthcare Management. - Kim, Jin-Nam; Oh, In-Hwan (Inquiry (00469580), 2024)
This study analyzes hospital bed capacity and resource allocation using inflow and outflow indices to identify disparities in bed utilization. The COVID-19 pandemic highlighted the need for effective healthcare management, particularly in the allocation of specialized beds such as those in intensive care units (ICU). Despite a high bed-to-population ratio, South Korea faces regional disparities in bed distribution, especially in Seoul, which accounts for 12.4% of the nation's hospital beds. Hospital beds were categorized based on the Medical Service Act, and the Relevance Index (RI) and Commitment Index (CI) were used to assess patient flow in 2019 across different bed types and functions. Data from the "Statistical Yearbook on the Usage of Medical Service by Region" provided insights into utilization patterns in tertiary referral hospitals, general hospitals, hospitals, and long-term care facilities. The analysis revealed high RIs for tertiary referral hospitals, indicating strong patient retention and minimal outflow, whereas lower RIs for long-term care hospitals suggested underutilization. Regional analysis within Seoul found a concentration of tertiary referral hospitals in the Southeast and a shortage of ICU beds in the Northwest and Southwest regions. The Inflow and Outflow Index confirmed significant patient inflow into tertiary referral hospitals, with some areas experiencing higher outflows, particularly for long-term care beds. These findings underscore the need for strategic hospital bed capacity management, prioritizing essential beds in underserved regions. Future research should incorporate more recent data and employ direct patient flow analysis to optimize resource allocation, addressing evolving healthcare demands, such as an aging population and new infectious diseases. This study offers valuable insights for regional health policy, aiming to enhance functional hospital bed management and improve overall healthcare resource utilization.